Optimisation Methods for Fast Restoration of Software-Defined Networks - Ali Malik; Benjamin Aziz; Mo Adda; Chih-Heng Ke (IEEE Access, 2017)
The increasing complexity of modern day networked applications and the massive demand on the Internet resources has reignited interest and concern in the underlying networking infrastructures and their ability to cope with such complexity and adapt to the demands of the business applications, particularly where such applications require a high degree of robustness and reliability. As a result, software-defined networking has emerged as a promising approach to the definition of network architectures that could carry a high degree of adaptability and robustness reminiscent of the future Internet. Fault tolerance and network updates are considered two of the current research challenges that hamper the growth of software-defined networking in this area. Therefore, this paper represents a step toward tackling these two issues in the context of single link failures. Our main contribution lies in the definition of new algorithms that aim to enhance the problem of finding alternative paths in large-scale networks with minimal cost and time-to-update factors. The new solution aims at increasing the efficiency of flow operation reduction during link failures. We evaluate our framework and show how its implementation results in improved efficiency.